Kekuatan Merek untuk Usaha Mikro Kecil Menengah (UMKM): (Brand Equity for Small Medium Micro Enterprises) - Esti Handayani; Muhamad Asari; Siti Mahmudah (LPPM Universitas Pelita Bangsa, 2021)
This study is to determine the strength of brands for Micro, Small and Medium Enterprises in South Kalimantan in the form of Image and Brand Identity and Brand Identity on Brand Love. This study used SEM AMOS analysis method with 150 respondents as consumers from the Alisa Khadijah ICMI Community throughout Indonesia. The results of his research show that the influence of Image and Brand Identity is in line with Brand Love. .